Multiple threats and conservation opportunities in the forgotten coral rag forests of Zanzibar, Tanzania - Robert Wild; Tim Caro; Nicholas E. Kolarik; Matt Clark; Yussuf Said; Tahir Haji (Biological Conservation, 2026)

A life-cycle framework reveals hidden costs of ecotourism - Tim Caro; Jeffrey Andrews; Monique Borgerhoff Mulder (Biological Conservation, 2026)

Black-and-white pelage as visually protective coloration in colobus monkeys - Ossi Nokelainen; Sandra Winters; Zeke Rowe; Fernando A. Campos; Eva C. Wikberg; Natasha Howell; Tim Caro (Behavioral Ecology and Sociobiology, 2024)
Conspicuous coloration is often seen as the evolutionary consequence of either sexual selection or warning predators visually about prey defences, although not all conspicuous species fit this paradigm. Exceptions include several species of colobus monkeys whose black-and-white coloration, characteristic of larger colobines, has never been explained. Here, using photographs of black-and-white colobus ( Colobus vellerosus ) taken in the wild, quantitative image analysis, and vision modelling (acuity-corrected feline, chimpanzee, and raptor vision), we provide evidence that their coloration provides distance-dependent camouflage in natural forest environments. At all viewing distances, black-and-white colobus monkeys blend into their environment because of their high chromatic overlap with the background when viewed by ecologically relevant predator vision models which have low visual acuities. Additionally, for chimpanzee and felid vision, there was evidence of edge disruption at longer viewing distances. Our comparative analyses of different species of colobines do not support an association between black-and-white coloration and larger body mass or group size, but this may simply be due to the limited number of species within the family. We reason that black-and-white colobines gain visually protective coloration through background matching against felids, and also benefit through disruptive coloration against felids and chimpanzees but rely on these protective coloration mechanisms less against raptors. Significance statement Conspicuous black-and-white coloration in colobus monkeys has long eluded an evolutionary explanation. Our research, employing photographs of colobus monkeys, image analysis, and vision modelling, unveils a novel approach to this coloration. We show that in their natural forest habitats, black-and-white colobus monkeys employ distance-dependent camouflage against ecologically relevant predators with low visual acuity, blending in with the background at increasing viewing distances. In summary, the evolution of black-and-white colobus coloration appears to be related to background matching against felids, with added benefits of disruptive camouflage against felids and chimpanzees, less so to raptors, offering fresh insights into the complex interplay of coloration and survival strategies in mammals.

Practical guide to coproduction in conservation science - Tim Caro; Jeffrey Andrews; Matthew Clark; Monique Borgerhoff Mulder (Conservation Biology, 2023)
We considered a series of conservation‐related research projects on the island of Pemba, Tanzania, to reflect on the broad significance of Beier et al.’s recommendations for linking conservation science with practical conservation outcomes. The implementation of just some of their suggestions can advance a successful coproduction of actionable science by small research teams. Key elements include, first, scientists and managers working together in the field to ensure feedback in real time; second, questions jointly identified by managers and researchers to facilitate engaged collaboration; third, conducting research at multiple sites, thereby broadening managers’ abilities to reach multiple stakeholders; and fourth, establishing a multidisciplinary team because most of the concerns of local managers require input from multiple disciplines.

Commentary to biodiversity and conservation Upgrading Birgus: lessons for invertebrate conservation - Tim Caro (Biodiversity and Conservation, 2022)
Coconut crabs Birgus latro have recently been reclassified from Data Deficient to Vulnerable on the IUCN Red List. This is a somewhat unusual case of temporal and spatial information being used to change the IUCN status of an arthropod and it draws attention to the paucity of biological data on most invertebrate species. To be listed, two or more scientific criteria need to be documented but such data are unavailable for many invertebrates. This raises the question as to whether certain invertebrates receive more scientific attention and are hence more likely to be listed if, like the coconut crab, they are large, slow-reproducing or a dual-biome species (characteristics which make them inherently vulnerable) and whether being an indicator or a flagship species is important.

When animal coloration is a poor match - Tim Caro (Evolutionary Ecology, 2021)
Biologists usually pursue the adaptationist paradigm in trying to explain the functional significance of animal coloration. Here I collate instances in which coloration may be a poor match in the context of background matching, Batesian mimicry, aposematism, and colour polymorphisms. This can occur because of trade-offs with other functions, relaxed selection from predation, or colour trait neutrality. Also, mechanistic, pleiotropic and chance genetic effects can all result in a poor match to the background environment or to signaling efficiently. While biologists implicitly recognise these constraints placed on adaptive coloration, they rarely explicitly acknowledge the heterodox notion that coloration might be under weak selection or no selection at all. Unfortunately, it is difficult to show this definitively, as illustrated in an investigation into the function of colour polymorphisms in coconut crabs.

Flash behavior in mammals? - Tim Caro; Hana Raees; Theodore Stankowich (Behavioral Ecology and Sociobiology, 2020)

Cheetahs modify their prey handling behavior depending on risks from top predators - Anne Hilborn; Nathalie Pettorelli; Tim Caro; Marcella J. Kelly; M. Karen Laurenson; Sarah M. Durant (Behavioral Ecology and Sociobiology, 2018)

Colour polymorphism in the coconut crab (Birgus latro) - Ossi Nokelainen; Martin Stevens; Tim Caro (Evolutionary Ecology, 2018)

The evolution of anterior coloration in carnivorans - Tim Caro; Hannah Walker; Sharlene E. Santana; Theodore Stankowich (Behavioral Ecology and Sociobiology, 2017)

The ecology of multiple colour defences - Tim Caro; Tom N. Sherratt; Martin Stevens (Evolutionary Ecology, 2016)

Wildlife and wildlife management in Tanzania - Tim Caro; Tim R.B. Davenport (Conservation Biology, 2016)
Tanzania, arguably mainland Africa's most important nation for conservation, is losing habitat and natural resources rapidly. Moving away from a charcoal energy base and developing sustainable finance mechanisms for natural forests are critical to slowing persistent deforestation. Addressing governance and capacity deficits, including law enforcement, technical skills, and funding, across parts of the wildlife sector are key to effective wildlife protection. These changes could occur in tandem with bringing new models of natural resource management into play that include capacity building, corporate payment for ecosystem services, empowering nongovernmental organizations in law enforcement, greater private‐sector involvement, and novel community conservation strategies. The future of Tanzania's wildlife looks uncertain—as epitomized by the current elephant crisis—unless the country confronts issues of governance, embraces innovation, and fosters greater collaboration with the international community.

Prey preferences of bushmeat hunters in an East African savannah ecosystem - Andimile Martin; Tim Caro; Christian Kiffner (European Journal of Wildlife Research, 2013)

Risk of injury and death from lightning in Northern Malawi - Jonathan Salerno; Lameck Msalu; Tim Caro; Monique Borgerhoff Mulder (Natural Hazards, 2012)

Conservation in the Anthropocene - TIM CARO; JACK DARWIN; TAVIS FORRESTER; CYNTHIA LEDOUX‐BLOOM; CAITLIN WELLS (Conservation Biology, 2012)

The functional significance of colouration in cetaceans - Tim Caro; Karrie Beeman; Theodore Stankowich; Hal Whitehead (Evolutionary Ecology, 2011)

Flagship species on covers of US conservation and nature magazines - Barbara Clucas; Katherine McHugh; Tim Caro (Biodiversity and Conservation, 2008)

Conservation Value of Multiple‐Use Areas in East Africa - TOBY A. GARDNER; TIM CARO; EMILY B. FITZHERBERT; TASILA BANDA; PUNIT LALBHAI (Conservation Biology, 2007)
Despite wide agreement that strictly protected areas (World Conservation Union categories I–III) are the best strategy for conserving biodiversity, they are limited in extent and exclude many species of key conservation importance. In contrast, multiple‐use management areas (categories IV–VI), comprising >60% of the world's protected‐area network, are often considered of little value to biodiversity conservation, particularly in Africa, where they typically contain few charismatic large mammals. We sampled small mammals, amphibians, birds, butterflies, and trees at 41 sites along a four‐step gradient of increasing human activity and decreasing conservation protection, from a well‐protected Tanzanian national park to nonintensive agricultural land. Although preliminary, our results indicate that species richness of these five taxa did not decline along this gradient, but different management areas, occupying areas of largely similar habitat, hosted distinct communities of each taxon. Differences in species composition in the absence of manifest differences in species richness highlight the importance of developing landscape‐scale conservation strategies and the danger of using either a limited suite of indicator taxa or umbrella species as surrogates for biodiversity. Although strictly protected areas perform a unique and vital conservation service in East Africa by protecting large mammals, areas that allow varied resource extraction activities still possess vital and complementary conservation value.

The Role of Research in Evaluating Conservation Strategies in Tanzania: the Case of the Katavi‐Rukwa Ecosystem - MONIQUE BORGERHOFF MULDER; TIM CARO; OMARI AYUBU MSAGO (Conservation Biology, 2007)
Strict protectionism, resource extraction, protected‐area community outreach, ecotourism, an integrated conservation and development program, comanagement schemes, and citizen‐science initiatives are all being used to help conserve the remote Katavi‐Rukwa ecosystem in western Tanzania. Biological and social research show that protectionism is successful in the conservation of large mammals but fails to capture diverse species communities; extractivism is appropriate for some resources but not for others; protected‐area outreach can be effective for some communities; and devolved control over wildlife, in conjunction with ecotourism and citizen science, has considerable potential in the area. The long‐term nature of the research provides the necessary time frame to evaluate outcomes of different conservation strategies, uncovers dynamics within communities that affect attitudes and responses to conservation initiatives, provides impartial recommendations because changing research personnel offers different viewpoints, and, probably most importantly, enhances trust among stakeholders. Currently, there are limited institutional mechanisms for ensuring the input of biological and social science in shaping conservation practice in Tanzania, and long‐term research can help informally bridge the gap

Assessment of Effectiveness of Protection Strategies in Tanzania Based on a Decade of Survey Data for Large Herbivores - CHANTAL STONER; TIM CARO; SIMON MDUMA; CHARLES MLINGWA; GEORGE SABUNI; MARKUS BORNER (Conservation Biology, 2007)
Considerable controversy surrounds the effectiveness of strictly protected areas that prohibit consumptive resource use. For Tanzania we compared temporal changes in densities of large herbivores among heavily protected national parks and game reserves, partially protected game‐controlled areas, and areas with little or no protection. Comparisons based on surveys conducted in the late 1980s and early 1990s versus the late 1990s and early 2000s showed three consistent patterns across the country. First, significant declines in the densities of large herbivores between these two snapshots in time overwhelmingly outnumbered significant increases in all protection categories. Second, more species fared well (increased significantly or showed no significant change) in strictly protected national parks than in areas with partial or no protection and in heavily protected game reserves relative to areas with no protection. Third, significantly more species fared poorly (densities declined or were too low to detect a decline) than fared well in areas with partial or no protection. Our results show that although heavy protection was generally more effective in maintaining large herbivore populations than partial or no protection, continued long‐term monitoring is needed in Tanzania to inform managers whether large herbivores are experiencing declining population trends even within heavily protected areas .

Use of Substitute Species in Conservation Biology - TIM CARO; JOHN EADIE; ANDREW SIH (Conservation Biology, 2005)
In conservation biology, researchers often want to study the reasons why an endangered population is faring poorly but are unable to study it directly for logistical or political reasons. Instead they study a species that substitutes for the one of concern in the hope that it will cast light on the conservation problem. Here we outline the assumptions underlying this approach. Substitutes can be different populations or species and may be chosen because they are similar biologically to the target or representatives of a constellation of species of which the target is one. They also may be used to develop a predictive model to which the conservation target can be related. For substitutes to be appropriate, they should share the same key ecological or behavioral traits that make the target sensitive to environmental disturbance and the relationship between population vital rates and level of disturbance should match that of the target. These conditions are unlikely to pertain in most circumstances and the use of substitute species to predict endangered populations' responses to disturbance is questionable.

Letters - Tim Caro (Conservation Biology, 2002)

Focal Species - Tim Caro (Conservation Biology, 2000)

Focal Species - Tim Caro (Conservation Biology, 2000)